LC Foto Le Corbusier Secret Photographer, Tim Benton - Wensing, Thomas (Architecture Image Studies, 2020)
This is a review of Tim Benton's LC Foto Le Corbusier Secret Photographer (2013), an immaculately researched and well-written book which covers the development of Le Corbusier’s photographic output. Le Corbusier had an ambiguous relationship with photography throughout his career; on the one hand he relied heavily on professional photography to promote his built work and support his discourse, but on the other hand he ‘maintained that photography was a stultifying activity, good only for lazy people’. In managing this image, he never allowed himself to be photographed holding a camera, while from 1916 and 1921, and again between 1936 and 1938, he literally took hundreds of photographs.